Structure elucidation and immunological activity of a novel pectic polysaccharide from the stems of Avicennia marina - Fang, Xubo; Chen, Xiaoe (European food research & technology, 2013)
The structure of HAM-3-IIb-II, an acidic pectic polysaccharide in Avicennia marina , was characterized in detail and the immunological activity was investigated in this study. The results showed that HAM-3-IIb-II contained Rha, Ara, Gal, Glc, and GalA in a molar ratio of 1:2.8:2.4:6.1 and that HAM-3-IIb-II is a type I rhamnogalacturonan with branches of arabinose chains, galactosyl chains, and arabinogalactosyl chains. The backbone of HAM-3-IIb-II is mainly composed of disaccharide repeat units, →4)-α- d -GalA-(1 → 2)-α- l -Rha p -(1→. These repeats are predominantly linked to the O-4 of 1,2,4-linked α- l -Rha p in the branches of arabinose chains, galactosyl chains, and arabinogalactosyl chains. HAM-3-IIb-II had a significant effect on lipopolysaccharide-induced B lymphocyte proliferation, but it had little effect on concanavalin A-induced T lymphocyte proliferation compared with the control. This study provides a foundation for the exploration and utilization of A. marina in the future.